2004
DOI: 10.1007/s11664-004-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of layer structure on performance of AlGaN/GaN high electron mobility transistors before and after passivation

Abstract: Intentionally undoped and three different, doped layer structures are used to investigate properties of AlGaN/GaN high electron mobility transistors (HEMTs) before and after SiN passivation. For unpassivated devices, the drain current, transconductance, cutoff frequency, and microwave output-power increase with increased doping level, in spite of an increase in the gate-leakage current. After passivation, an overall performance improvement of all devices occurs. The passivation-induced sheet charge decreases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In agreement with this observation, in our case, we do not see a significant improvement in the DC characteristics of the devices simply due to passivation. This improvement has been observed by other workers (10,11). Typical results from pulsed electrical characterization are shown in Figs.…”
Section: Resultssupporting
confidence: 85%
“…In agreement with this observation, in our case, we do not see a significant improvement in the DC characteristics of the devices simply due to passivation. This improvement has been observed by other workers (10,11). Typical results from pulsed electrical characterization are shown in Figs.…”
Section: Resultssupporting
confidence: 85%
“…Figure 4 shows the two-terminal gate-source leakage currents that were typical for the undoped and doped GaN/AlGaN/GaN HFETs from both sets. Partially higher leakage currents for the doped devices compared with the undoped ones were expected [15]. However, remarkably higher leakage currents (about four orders of the magnitude) were measured on the longdip-treated devices.…”
Section: Resultsmentioning
confidence: 80%
“…The GaN cap layer was chosen to enhance the effective Schottky barrier height [13,14]. The doping level of 5 × 10 18 cm −3 followed from our previous study as an optimal value for modulation-doped GAN HFETs [15].…”
Section: Methodsmentioning
confidence: 99%
“…However, unpassivated AlGaN / GaN HEMTs with low current dispersion were recently presented. [4][5][6][7] Devices prepared on intentionally doped heterostructures were used in these studies. Also, another study reported on improvements in the performance of unpassivated and passivated devices based on a doped material structure compared with the performance of those based on an undoped structure.…”
mentioning
confidence: 99%